The Use of Code-Switching by Secondary School Students’ in English Speaking Class - Saidah Mardliyah; Nailul Authar; Mujad Didien Afandi (International Journal of English Education and Linguistics (IJoEEL), 2026)
This study aims to investigate the use of code-switching, a linguistic phenomenon in which a person switches languages or language varieties alternately in a conversation or interaction among secondary school students in Sidoarjo. This study used a qualitative approach, utilising interviews to identify the affecting factors behind students' code-switching and explore students' perceptions of the function of code-switching in the English classroom. The findings show that code-switching significantly enhances students' speaking instruction in a rural, bilingual environment by recognising code-switching as a learning tool and a reflection of students' needs. In addition, students reported positive experiences, showing increased motivation and engagement. This research highlights students' language gaps to transform into a fun interaction tool in classroom learning.